Reproduction and growth in a Neotropical arboreal mouse: Oecomys rutilus (Sigmodontinae: Cricetidae) in French Guiana - Catzeflis, François (Biota Neotropica, 2019)
Abstract: Postnatal growth and development of the small Neotropical mouse Oecomys rutilus (Sigmodontinae: Cricetidae) were investigated from birth to day 143, in the laboratory. Morphometric measurements at age of 3 days, of both sexes combined, revealed body weight to be 3.4 ± 0.3 g, mean tail length as 27.4 ± 1.1 mm, and mean hind foot length as 9.3 ± 0.7 mm. Body weight was found to increase steadily until at least 69 days, whereas the instantaneous growth rates of other measurements declined earlier: the daily growth of hind foot length declined to a minimum at age of 24 days, and the growth of tail and of ear declined by the age of 33 days. Average litter size for 12 captive births was 2.5, ranging from 2 to 3. The preserved eye crystalline lens was weighted in 23 captive-born animals of known age, allowing a rough estimate of the age of reproduction in wild-caught animals. Based on the inferred relation between eye-lens weight and age, the youngest reproductive (pregnant) wild-caught females had an estimated age of 90 and 95 days.